Educational Management for Migrant Workers' Children in Early Childhood Centers Within Schools in Lamphun Province - Runnapab, Suteepat; Panyadee, Chalermchai; Kaewthip, Somkid; Ek-aem, Bongkochmas; Tantar, Thammaporn (Dhammathas Academic Journal, 2026)
This research aimed to investigate the management model of education and the effectiveness of education management for migrant’s children of early childhood schools development center schools, Lamphun Province. This research was quantitative research method that used questionnaire to collect data. There were 175 population, and the sample group were 122 schools. Data analysis was statistics including mean and standard deviation. The research result found that teachers/educational personnel were the most (=4.17, S.D 0.55) with an average value at a high level, the educational institution administrators (=4.08, S.D 0.58) with an average score at a high level, the educational institution committee (=3.91, S.D 0.59) with an average score at a high level, the government's educational policy (=3.89, S.D 0.49) with an average score at a high level, the network organization (=3.85 S.D 0.64) with an average score at a high level, the technology and teaching media (=3.68, S.D 0.69) with an average score at a high level, the participation of parents/alumni associations (=3.52, S.D 0.74) with an average score at a high level, and the budget used for curriculum management (=3.17, S.D 0.73) with an average score at a moderate level, respectively.Moreover, the research result on the effectiveness of education management for migrant’s children of early childhood schools development center, Lamphun province found that emotional/mental development was highest (=4.39, S.D 0.54) with an average value at a high level , followed by physical development (=4.31, S.D 0.54) with an average value at a high level , social development (=4.24, S.D 0.53) with an average value at a high level, and intellectual development (=4.07, S.D 0.55) with an average value at a high level, respectively.